2009
DOI: 10.1111/j.1600-079x.2009.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of melatonin’s multiple mitochondrial levels of protection against mitochondrial Ca2+‐mediated permeability transition and beyond in rat brain astrocytes

Abstract: Melatonin protects cells against various types of oxidative stress-induced apoptosis due primarily to its ability to effectively scavenge pathological and disease condition-augmented generation of mitochondrial reactive oxygen species (mROS). Once produced, mROS indiscriminately damage mitochondrial components and more importantly they crucially activate directly the mitochondrial permeability transition (MPT), one of the critical mechanisms for initiating post mitochondrial apoptotic signaling. Whether or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 150 publications
(43 citation statements)
references
References 67 publications
(73 reference statements)
1
33
1
Order By: Relevance
“…These findings are in agreement with our previous works reporting that MEL prevented UVB cell death by stabilizing the mitochondrial membrane potential and by inhibiting cytochrome c release [6,35]. Many of the beneficial effects of MEL administration may depend on its action on mitochondria [4648] where high concentrations of MEL were found. In fact, there is evidence that mitochondria may have the capacity to synthesize and metabolize MEL [49,50].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with our previous works reporting that MEL prevented UVB cell death by stabilizing the mitochondrial membrane potential and by inhibiting cytochrome c release [6,35]. Many of the beneficial effects of MEL administration may depend on its action on mitochondria [4648] where high concentrations of MEL were found. In fact, there is evidence that mitochondria may have the capacity to synthesize and metabolize MEL [49,50].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we not only demonstrated the co-localization of delivered mitochondria and endogenous mitochondria in host cells but also showed that the overloading of [Ca 2+ ]m with or without inducing oxidative stress was dramatically reduced in both types of treated cells. These findings suggest that steric hindrance resulting from the translocation of foreign mitochondria interfered with the endogenous MFN2-ER connection and led to a reduction in the excessive uptake of [Ca 2+ ]m, which in turn triggered mitochondrial permeability transition pore opening and cell death [28]. Recently, an ER-mitochondrial disorder was considered to be involved in the pathogenesis of Alzheimer's disease [29,30], although it remains unidentified in other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the higher concentration of the free radical scavenger melatonin in mitochondria relative to some other subcellular organelles [65], melatonin’s ability to detoxify ROS in both the intermembrane space and matrix is certainly feasible and has been documented [115]. Judging from the greater efficacy in protecting mitochondria from damage when compared to synthetically-produced, mitochondria-targeted antioxidants [116,117], melatonin itself has been classified as a mitochondria-targeted antioxidant [73,81,118] and may also have a transporter to aid in its transfer into the cell and possibly into the mitochondrial matrix [119,120], which permits it to concentrate in this organelle [65,73,81].…”
Section: Cancer Initiation: Genomic Damage and Instabilitymentioning
confidence: 99%